2019
DOI: 10.1177/0146167219861438
|View full text |Cite
|
Sign up to set email alerts
|

Keeping the Goal in Sight: Testing the Influence of Narrowed Visual Attention on Physical Activity

Abstract: Rates of physical inactivity continue to rise in the United States. With this work, we tested the efficacy of a strategy affecting the scope of visual attention designed to promote walking as a form of exercise. Specifically, we examined the influence of narrowed attention on the frequency (Studies 1a, 1b, and 3) and efficiency (Studies 2 and 4) of physical activity in general (Studies 1 and 2) and within exercise bouts measured across multiple days (Studies 3 and 4). We provide convergent evidence by investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In a causal relationship, the literature suggests that people with high levels of physical activity substantially reduces the risk of developing cognitive impairment ( Blondell et al, 2014 ). Likewise, high levels of walkability can increase physical activity by up to 57% by providing environments with a diversity of options and access to businesses and services in the neighbourhood, parks with adequate structures for use, regular and well-maintained sidewalks, and well-connected streets (Reis et al, 2013; Balcetis et al, 2020 ). Thus, statistical models interpreted in isolation may establish that genuine relationships between variables are to be discarded ( Mc Shane et al, 2019 ; Wasserstein et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a causal relationship, the literature suggests that people with high levels of physical activity substantially reduces the risk of developing cognitive impairment ( Blondell et al, 2014 ). Likewise, high levels of walkability can increase physical activity by up to 57% by providing environments with a diversity of options and access to businesses and services in the neighbourhood, parks with adequate structures for use, regular and well-maintained sidewalks, and well-connected streets (Reis et al, 2013; Balcetis et al, 2020 ). Thus, statistical models interpreted in isolation may establish that genuine relationships between variables are to be discarded ( Mc Shane et al, 2019 ; Wasserstein et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, eye-catching environments improve the intensity of physical activity (Balcetis et al, 2020). We told survey respondents about two different styles they might use when they exercise.…”
Section: Visual Experiences Encourage Physical Activity In Walkable Nmentioning
confidence: 99%
“…Among a primarily Black sample of New York residents living in low-income housing developments, those who reported that their neighborhoods contained more visually interesting things that caught their attention were more physically active than those who believed their neighborhoods contained fewer interesting things (Balcetis et al, 2020). This was true among residents in San Francisco, Washington, D.C., Boston, and other New York City neighborhoods as well.…”
Section: Visual Experiences Encourage Physical Activity In Walkable Nmentioning
confidence: 99%
See 2 more Smart Citations